1990
DOI: 10.1037/0022-006x.58.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric profile of posttraumatic stress disorder, anxious, and healthy Vietnam veterans: Correlations with psychophysiologic responses.

Abstract: Three groups of Vietnam combat veterans, posttraumatic stress disorder (PTSD, n = 25), anxious (n = 7), and healthy (n = 18), completed a battery of psychometric tests. Measurement of psychophysiologic responses to imagery of individualized combat experiences followed the psychometrics. The PTSD Ss differed significantly from the healthy Ss on almost all measures but showed fewer differences from the anxious Ss. The typical PTSD S was characterized as anxious, depressed, prone to dissociation, and external in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
2
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 33 publications
7
60
2
2
Order By: Relevance
“…Lower physiological reactivity in the high dissociation group is surprising in light of the fact that most of the members of this group had PTSD symptoms. This finding contrasts with previous findings of generally higher physiological reactivity in subjects with PTSD (23)(24)(25)(26). The response of subjects in the high dissociation group may provide evidence of a specific PTSD subtype of highly dissociative individuals who may respond with a general physiological numbness.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Lower physiological reactivity in the high dissociation group is surprising in light of the fact that most of the members of this group had PTSD symptoms. This finding contrasts with previous findings of generally higher physiological reactivity in subjects with PTSD (23)(24)(25)(26). The response of subjects in the high dissociation group may provide evidence of a specific PTSD subtype of highly dissociative individuals who may respond with a general physiological numbness.…”
Section: Discussioncontrasting
confidence: 57%
“…However, at least with regard to the physiological data, previous findings do not support this conclusion. Orr et al (23) found physiological differences between combat veterans with PTSD and those without PTSD. The mean Beck Depression Inventory scores of their PTSD subjects were comparable to the Beck inventory scores of the subjects in our high dissociation group.…”
Section: Discussionmentioning
confidence: 99%
“…Details obtained for all events included: location of the event, sensory experiences, and descriptive information (e.g., date, duration, others present during the event). Consistent with previously employed script-driven imagery procedures (e.g., Orr et al, 1990;Pitman et al, 1987), participants also completed a checklist of physiological sensations experienced during the events. The experimenter used this information to audio-record 30-sec narratives for each of the scripts, which were then used during the script-driven imagery procedure.…”
Section: Methodsmentioning
confidence: 99%
“…This assessment method is well-established for use with script-driven imagery procedures (e.g., Orr et al, 1990;Pitman et al, 1987). Following the presentation of each script, participants were asked to provide ratings of anger, disgust, and anxiety by placing an "X" on three separate 100 mm rating lines ranging from 0 (no anger/disgust/anxiety) to 100 (extreme anger/disgust/anxiety).…”
Section: Subjective Units Of Distress Scale (Suds)mentioning
confidence: 99%
“…Twelve veterans with PTSD had significantly elevated scores on the Zung depression scale and on the Spielberger State-Trait Anxiety Inventory, com pared to combat veterans without PTSD and noncombat psychiatric inpatients. Compara ble findings with the Beck Depression Inven tory and the State Trait Anxiety Inventory are described by Orr et al [7], who contrasted 25 Vietnam combat veterans, suffering from PTSD. with 7 anxious and 18 healthy combat veterans.…”
Section: Introductionmentioning
confidence: 95%